Direct inlet negative ion chemical ionization tandem mass spectrometric analysis of triacylglycerol regioisomers in human milk and infant formulas - Fabritius Mikael; Linderborg Kaisa M; Tarvainen Marko; Kalpio Marika; Zhang Yumei; Yang Baoru (Elsevier BV, 2022)
A previously developed direct inlet tandem mass spectrometric method for analysis of triacylglycerol (TAG) regioisomers was updated and validated for operation with current instrumentation with improved sensitivity and throughput. TAG regioisomers in pooled Chinese and Finnish human milk samples, two bovine milk samples and 11 infant formulas were identified and quantified. A total of 241 TAG regioisomers were identified and quantified, consisting of over 60 mol% of all TAGs in the human milk samples. The infant formulas deviated largely from human milk in regioisomeric composition of TAGs. In the Finnish and Chinese human milks, the most abundant ones were 1,3-dioleoyl-2-palmitoylglycerol (OPO; 7.4 and 8.8 mol% of all TAGs) and 1(3)-linoleoyl-2-palmitoyl-3(1)-oleoylglycerol (LPO; 4.7 and 8.3 mol% of all TAGs). In the infant formulas 1,2(2,3)-dioleoyl-3(1)-palmitoylglycerol (OOP) and 1(3)-linoleoyl-2-oleoyl-3(1)-palmitoylglycerol/1(3)-palmitoyl-2-linoleoyl-3(1)-oleoylglycerol (LOP/PLO) were more abundant than OPO and LPO. The differences between human milk and infant formula prompt for further development of current formulas.